Karakter Semangat Kebangsaan pada Ritus Grebeg Pancasila untuk Siswa Sekolah Dasar - Septinaningrum Septinaningrum; Tursinawati Tursinawati (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2023)
This mini research aims to describe the character analysis of the national spirit in the Grebeg Pancasila rites in Blitar City. The approach and type of research used is descriptive qualitative with library research methods (literary research) and field studies. Data collection techniques with interviews as well as document review and recording. Analysis of the data qualitatively interactive model.The character of the national spirit in marketing in the Grebeg Pancasila rite. This can be seen from the five Grebeg Pancasila rites starting from Pusaka Nagari Bedholan, Tirakatan Night, Cultural Ceremony, Kirab Gunungan Lima and ending with Pancasila Kenduri which is full of meaning and character content originating from religion, Pancasila, culture and Indonesia's national education goals.The results of the study and analysis of the Grebeg Pancasila rites can be used to develop the Grebeg Pancasila learning model. What can be developed is adapting the five Grebeg Pancasila processions into the syntax of a learning model to develop character that can be implemented in Elementary Schools/Madrasah Ibtidaiyah.